The The Effect of a Creative-Productive Model Using a Flipchart on the Memory Retention of Fifth-Grade Students in the IPAS Subject - Tri Puji Astuti, Bibit; Sukmarani, Dhuta; Istiningsih, Galih (Universitas Muhammadiyah Magelang, 2026)
This study aims to determine the effect of the Productive Creative Model assisted by flipchart media on the memory of fifth-grade students in the IPAS subject at SD Negeri Magelang 6. The method employed in this study is a quasi-experimental design using the Non-Equivalent Control Group Design. The samples for this study consisted of class 5B as the experimental group and class 5A as the control group, each comprising 24 students at SD Negeri Magelang 6. Data were collected through essay tests and observations. Prerequisite tests in this study included the Shapiro-Wilk normality test and the Levene homogeneity test. Hypothesis analysis was conducted using the Independent Sample T-test. The data obtained from this study indicate a significant influence of the creative productive model and flipchart media on the memory of fifth-grade students. Through the Independent Sample T-test, a p-value of 0.000 (< 0.05) was obtained. Quantitatively, achievement differences were observed, with the mean pretest score of the experimental class at 39 and the control class at 31.5, while the mean posttest score for the experimental class reached 73.71 and the control class at 70.92. These results validate a significant difference between the pretest and posttest outcomes. Given that the t-calculated value of -6.020 falls outside the H₀ acceptance region (t-table 2.012), it can be concluded through this study that the creative productive model effectively influences the memory of fifth-grade students in the IPAS subject.